Modelling the impact of rural land use scenarios on water management: a FREEWAT approach to the Bakumivka catchment case study, Ukraine - Grodzynskyi, Mykhailo; Svidzinska, Daria (Acque Sotterranee - Italian Journal of Groundwater, 2017)
The Bakumivka River's catchment, Ukraine serves as a case study to the application of FREEWAT to the ground and surface water management. The main objective of the study is to find out the optimal spatial distribution of the water supplied to the farms by modifying the land cover pattern of the catchment. An integrated numerical model was developed to provide quantitative estimates of the water budget components. The model includes four model layers, representing the main hydrostratigraphic units, different types of boundary conditions assigned along the area's boundaries, major components of the water balance introduced through source and sink layers. It was implemented through the FREEWAT software. Three water management scenarios were developed in order to compare different spatial patterns of land cover and distribution of water within the Bakumivka River's basin. The scenarios represent continuum from market oriented pattern to environmentally sounding pattern of land cover. The objective of the modeling exercise is to obtain mass balances and maps representing three scenarios of water management. Each map shows distribution of the areas where the water balance is optimal, insufficient (dry) or excessive (wet) for vegetation (land cover) of particular type.The simulation shows that changing spatial land cover pattern is an effective measure to reduce water supply to the farms, however it does not prevent water logging in the areas adjacent to the flood plains and drying on summer stress periods in lands of sandyloam soils. Irrigation should be excluded in the areas with sandy and sandyloam soils. The flood plain with peat bogs despite the high water head in spring and late summer stress periods should be irrigated to prevent peat fires. The intrusion of eco-corridors to the land cover pattern in the catchment is positive from ecological perspective, but could prevent drainage causing water logging in the arable lands.